Parental Marital Quality and School Bullying Victimization: A Moderated Mediation Model of Parent–Child Attachment and Child Gender - Guojie Peng; Qiwen Liang; Siying Li; Xin Li; Weiqi Mu; Mingjie Zhou (Children, 2025)
Background/Objectives: School bullying is a significant issue that negatively impacts children’s well-being, emphasizing the need to identify family-related factors contributing to bullying victimization. This study explored the potential link between parental marital quality and school bullying victimization by employing a moderated mediation model. Methods: Parent–child attachment, measured separately as father–child and mother–child attachment, was tested as a mediator, with child gender included as a moderator. Data were collected from both children and their mothers, comprising 358 mother–child pairs recruited from three primary schools in suburban Beijing, China. Results: Results revealed that greater parental marital quality was associated with a lower risk of bullying victimization, with father–child attachment mediating this relationship. Furthermore, child gender moderated the mediating effect of father–child attachment, such that the indirect pathway from parental marital quality to bullying victimization through father–child attachment was statistically significant for girls but not for boys. Conclusions: These findings highlight the importance of father–child attachment in preventing bullying victimization and suggest that gender-sensitive implications may be necessary.